2001
DOI: 10.1007/s001340100962
|View full text |Cite
|
Sign up to set email alerts
|

Early prognosis in severe sepsis via analyzing the monocyte immunophenotype

Abstract: A single blood sample test obtaining the absolute monocyte and CD13-HLADR subpopulation count in the first days of admission could contribute to simplifying the classification of patients with severe sepsis into high- and low-mortality risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 0 publications
2
18
1
2
Order By: Relevance
“…It has been described as a predictor of an increased risk for infectious complications in trauma, pancreatitis or surgery [10][11][12][13]. In severe sepsis and septic shock, although previous studies have included a limited number of patients, first results tended to indicate that diminished monocyte HLA-DR may be a good marker regarding mortality prediction [14][15][16][17]. In line, the results of the present study agreed with those preliminary observations.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…It has been described as a predictor of an increased risk for infectious complications in trauma, pancreatitis or surgery [10][11][12][13]. In severe sepsis and septic shock, although previous studies have included a limited number of patients, first results tended to indicate that diminished monocyte HLA-DR may be a good marker regarding mortality prediction [14][15][16][17]. In line, the results of the present study agreed with those preliminary observations.…”
Section: Discussionsupporting
confidence: 94%
“…Interestingly, the level of monocyte HLA-DR expression is now proposed as a reliable marker of immunoparalysis both to assess its magnitude and its persistence over time [7,9]. In different clinical contexts, low HLA-DR expression predicts septic complications [10][11][12][13] and correlates with an increased risk for fatal outcome [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In the past, several studies using flow cytometric techniques showed that HLA-DR expression as well as IL-12 and TNF-␣ synthesis by MOs are reduced after different types of trauma [8,11,28,29]. These studies, however, did not simultaneously investigate stimulated whole blood cultures under comparable conditions.…”
Section: Discussionmentioning
confidence: 93%
“…T-cell infiltrates, but not bone marrow cellularity, may play a key role in the pathogenesis of HHH. Additional studies are necessary to clarify the possible role of the bone marrow microenvironment in the pathogenesis of HHH, to characterize the activation status of macrophages in HHH (33), and to investigate in detail the role of T lymphocytes and their associated cytokine profile (Th1/ Th2-immune response) (34 …”
Section: Resultsmentioning
confidence: 99%